Electrolysis of Metal Coating Industrial Waste Using Carbon Electrode to Reduce Metal Levels of Chromium (Cr), Zink (Zn), and Cadmium (Cd) - Zul Alfian; Valentina Hutagalung (Talenta Publisher, 2024)
The wastewater from the metal coating industry comprises hazardous and poisonous metals, necessitating the reduction of its concentration before its release into water. The typically employed chemical technique involves the addition of Poly Aluminium Chloride (PAC), which causes the hazardous element to accumulate due to the subsequent application of Poly Aluminium Chloride (PAC). Next, the metal content is measured and determined using the atomic absorption spectrophotometry. This study employed the electrolysis technique utilizing carbon electrodes. The liquid waste undergoes electrolysis with voltage changes of 8, 11, 14, and 17 volts for 2 hours. The investigation yielded the optimal voltage for minimizing the metal content. The voltage applied to the metal is 17 volts. The reduction in the concentrations of Cr, Zn, and Cd metals achieved with the optimal voltage is 63.02%, 70.02%, and 80.14%, respectively.